2021
DOI: 10.3390/app11104520
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Antimicrobial Nanoparticles and Their Applications in Biomedical Engineering

Abstract: Antibiotic resistance is a major threat to public health, which contributes largely to increased mortality rates and costs in hospitals. The severity and widespread nature of antibiotic resistance result in limited treatments to effectively combat antibiotic-resistant pathogens. Nanoparticles have different or enhanced properties in contrast to their bulk material, including antimicrobial efficacy towards a broad range of microorganisms. Their beneficial properties can be utilised in various bioengineering tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 139 publications
0
27
1
Order By: Relevance
“…One of the topics of the currently ongoing scientific debate on the toxicity of NPs is their potentially destructive effect on the functioning of microorganisms. Despite the huge amount of scientific data in this field, there is still controversy about the impact of NPs on microorganisms, especially these newly designed engineered NPs [7,8,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the topics of the currently ongoing scientific debate on the toxicity of NPs is their potentially destructive effect on the functioning of microorganisms. Despite the huge amount of scientific data in this field, there is still controversy about the impact of NPs on microorganisms, especially these newly designed engineered NPs [7,8,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Among the several proposed mechanisms of action of metallic NPs on bacterial cells is the induction of oxidative stress by generating ROS [8,9,24,26]. Although this phenomenon has been reported in many publications, information on the individual radical forms induced by metal NPs and their combined action in disrupting cellular redox cycles remains fragmentary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srinivas and Reddy [73] also demonstrated that the amount of Aerva javanica residues extracted with methanol was higher when compared with other solvents and leaf and flower yielded larger amounts of extracts. Methanolic extracts of leaf and flower have shown a wide range of phytochemicals and higher antibacterial activity and among all strains, Pseudomonas aeruginosa and Bacillus subtilis susceptibility was greater to extracts [74].…”
Section: Discussionmentioning
confidence: 99%
“…AVNP and antimicrobial nanomaterials have been shown to possess a range of biomedical functionalities [21][22][23][24]. AVNP with intermetallic/multi-elemental compositions have shown to actively counteract a range of bacterial pathogens [25,26], H5N1 and H1N1 influenza A viruses and the severe acute respiratory syndrome coronavirus (SARS-CoV) [27].…”
Section: Introductionmentioning
confidence: 99%